2017
DOI: 10.1111/twec.12583
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral trust and trade: Evidence from China

Abstract: By changing transaction costs, trust can be a determinant of interregional economic exchange. Based on data sets of bilateral trust and trade at provincial level in China, this study investigates the trust–trade relationship empirically. As a channel of affecting bilateral trade, bilateral trust is incorporated into gravity models. By controlling for institutional quality, labour migration and other economic indicators, the baseline results show that the bilateral trust is positively correlated with the bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
(72 reference statements)
2
22
0
Order By: Relevance
“…In addition to this, there is now extensive evidence that interdependent bilateral trade reduce interstate political conflict (Gleditsch, 2008;Jervis, 2002;Xing & Zhou, 2018). For example, liberal theorists identify that increased bilateral trade strengthens cooperation by increasing the opportunity cost of political conflicts (Maoz, 2009;Polachek et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to this, there is now extensive evidence that interdependent bilateral trade reduce interstate political conflict (Gleditsch, 2008;Jervis, 2002;Xing & Zhou, 2018). For example, liberal theorists identify that increased bilateral trade strengthens cooperation by increasing the opportunity cost of political conflicts (Maoz, 2009;Polachek et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to being related to the broader literature examining the effect of domestic institutions on the patterns of international trade specialization (Levchenko, 2007;Nunn, 2007;Manova, 2013), this paper contributes to a growing body of literature on the international trade effect of trust. Pioneer studies in this literature consider bilateral trust between exporter and importer to be "transaction cost reducing" and argue that enhancing bilateral trust between both parties will increase bilateral trade (Guiso, Sapienza and Zingales, 2009;Yu, Sjoerd and de Haan, 2015;Spring and Grossmann, 2016;Xing and Zhou, 2018;Melitz and Toubal, 2019). To test this hypothesis, available studies regress bilateral trade volume on bilateral trust.…”
Section: Introductionmentioning
confidence: 99%
“…Most were reallocated within the province and only 7.9% (1.4 million) were sent outside the province. This implies that the inter-province flow of SDYs, which is highlighted in the studies of Kinnan, Wang, and Wang (2018) and Xing and Zhou (2018), account for only a small part of the movement. Among the 1.4 million inter-province SDYs, three municipalities-Beijing, Tianjin, and Shanghaicontributed 87.3% of the total (or 0.87 million).…”
Section: Send-down Movement: a Brief Historymentioning
confidence: 99%
“…They found that temporary migration due to the program created lasting inter-province links, which resulted in increased access to migration decades after the program ended. Xing and Zhou (2018) provided evidence that SDYs became familiar to the residents living in their sent down regions. Henceforth, bilateral trust and trade between the source province and the destination province increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation